Food Selectivity in Children with Autism Spectrum Disorder: A Statistical Analysis in Southern Italy - Angela Alibrandi; Agata Zirilli; Federica Loschiavo; Maria Cristina Gangemi; Alessandro Sindoni; Graziella Tribulato; Roberto Lo Giudice; Fausto Famà (MDPI AG, 2023)
This paper focuses on autism spectrum disorder (ASD) and food selectivity, both of which are prevalent in the pediatric population. In this context, the authors paid attention to food selectivity and its possible correlation with the atypicality of sensory processes, outlining the useful rehabilitation treatments to draw on. This research included the parents or caregivers of pediatric patients diagnosed with autism spectrum disorder and placed within a therapeutic clinic. The sample is composed of 111 children, males and females, aged between 2 and 10 years, and includes 60 children diagnosed with autism and 51 children with normotypical development, similar in characteristics but without the disorder. The standardized questionnaire, "Brief Autism Mealtime Behavior Inventory", was developed to examine behavior during meals, especially in children with ASD. The "Brief Sensory Profile", and the "Child Oral and Motor Proficiency Scale", were also administered. The results obtained from the analysis lead to evidence of eating and food selectivity difficulty. Additionally, our study demonstrates that food selectivity can be caused by extreme sensory modulation and sensory problems related to the smell, texture, color, and temperature of food. In fact, the results obtained emphasize the correlation between food selectivity and the sensory domains of taste and smell. Furthermore, this research highlights a correlation between motor skills and eating skills, particularly regarding food selectivity, which is closely associated with atypical and disruptive behaviors during meals.